Impact Evaluation in Practice, First Edition - Gertler, Paul J. (World Bank, 2012)
The Impact Evaluation in Practice handbook is a comprehensive and accessible introduction to impact evaluation for policymakers and development practitioners. The book incorporates real-world examples to present practical guidelines for designing and implementing evaluations. Readers will gain an understanding of the uses of impact evaluation and the best ways to use evaluations to design policies and programs that are based on evidence of what works most effectively. The handbook is divided into three sections: Part One discusses what to evaluate and why; Part Two outlines the theoretical underpinnings of impact evaluation; and Part Three examines how to implement an evaluation. Case studies illustrate different methods for carrying out impact evaluations.